PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KONTEKSTUAL PADA MATERI PENCEMARAN LINGKUNGAN UNTUK MEMBERDAYAKAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VII SMP - Adinar Adinar; Wan Syafi’i; Fitra Suzanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the level of validity of students' worksheets (LKPD) based on contextual materials on environmental pollution to empower the creative thinking abilities of Class VII SMP. This research was conducted in two places, namely validation by the validator carried out in the Biology Education Study Program, Faculty of Teacher Training and Education, University of Riau and a limited trial was carried out at SMPN 6 Bangko Pusako in May-October 2019. This type of research is development research using the ADDIE model conducted to the development stage (development). There are 4 LKPD developed. Data collection instruments in this study were LKPD validation sheets, and questionnaire respondents. After LKPD is developed, it is then validated by 5 validators. After that, the first trial was conducted on 15 biology education students from the Teaching and Education Faculty of Riau University, and the second trial was conducted on 20 Class VII students at SMPN 6 Bangko Pusako. Contextual-based class VII student worksheets (LKPD) have been successfully developed with a very valid category.Key Words : Development, LKPD, Contextual, Creative Thinking Ability.